LITERARY DISCOURSE ANALYSIS FOR REPRESENTATION OF INFORMATION: ethical bias - Caprioli, Mariana da Silva [UNESP]; Ernesto de Moraes, Joao Batista [UNESP] (Univ Federal Campina Grande, 2017)
This is on the assumption that the discursive process is rich in tools to decode the discursive formations in literary discourse, then objectively observe the contribution of Literary Discourse Analysis for the retrieval of information from narrative texts of fiction in information unit, through explanations on the French approach discourse analysis, some important concepts, and also what the ethical role of the professional who plays, as it has committed to represent the best content for your user to retrieve more accurately, in addition to meeting with other ethical issues that the profession imposes. It is known that the Representation and Information Retrieval are processes in micro environment in order to reach the Organization and Knowledge Representation, and that is the universe in which the research fits. The final considerations of this research expected to be found in master's thesis under development.
Keywords: Discourse Analysis; Literary Discourse Analysis; Representation of Information; Ethic; Knowledge Organization